O Potencial formativo do desenvolvimento local na sociedade planetária. Do dualismo dos saberes do mundo - Paolo Orefice (Firenze University Press, 2010)
This paper is a specific contribute in matter of human development, within the scientific research at the international level. At the present time the priority is to question ourself about which right model of human development and inhabited territories is necessary , which are the constitutive components and how these operate, the principal aim and of whom, which is the aim and expected outcomes for the planet and for its inhabitants. Starting from these answers, obviously , we don't think to resolve the discussion about this matter, in the world the discussion about this specific problem has still opened, my be We can reflect on the sense, on educational outcomes can be on human development and, therefore, of which education and of which knowledge for the men and the women of our planet we are speaking.